Validation of the Indonesian version of the self-compassion scale for youth using Rasch model analysis - Ramadhan, Restu Afdal; Ahman, Ahman; Solehuddin, M. (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
Adolescence is a phase marked by stress, emotional instability, and low self-esteem, often leading to self-criticism and social withdrawal. To cope with these challenges, adolescents need self-compassion to maintain self-kindness and achieve better psychological well-being. This study aims to measure adolescent self-compassion using the Self-Compassion Scale for Youth (SCSY), a 17-item scale developed to suit the competencies of adolescents, as the original Self-Compassion Scale (SCS) is less applicable for this age group. A quantitative survey design was employed, with data from 105 high school students (aged 16-17, predominantly Sundanese, residing in rural areas) analyzed using JASP and Winstep for Rasch Model measurement. Results indicated that the SCSY demonstrated acceptable validity and reliability, confirming its suitability for adolescent self-compassion measurement. Findings underscore the importance of self-compassion in fostering emotional stability and resilience, suggesting that school-based guidance and counseling could benefit from incorporating self-compassion training to enhance mental health support for adolescents. The SCSY's tailored approach facilitates early detection of self-compassion levels, enabling counselors to provide targeted interventions that align with adolescents' developmental needs.